Skill Improvement of Explanation Text Writing By Using Series Image Media in Class XI IPA 2 Students of SMA Negeri 7 OKU - Idyawati, Novi; Wardiah, Dessy; Fitriani, Yessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The purpose of this study is to explain the process and results of improving explanatory text writing abilities in XI grade SMA Negeri 7 OKU using serial image media. At SMA Negeri 7 OKU class XI IPA 2, this Classroom Piercing Study was performed for a total of 36 individuals, with 36 students consisting of 14 boys and 22 girls. This analysis is an action study consisting of two periods of preparing, executing, observing, and reflecting with each cycle. Activities and skills of writing explanatory text by observation sheets, writing explanatory text, and documentation are the data taken throughout this review. The result of this study increased from the first cycle 44.5% increased in the second cycle 84,125. The results of this study, it was seen that through serialized image media can improve the writing skills of students' explanation texts